"Syrup of music". (Journal of Parents and Teachers, 2014)
This article explains the multiple benefits that music brings to our organism. Through music, the affective, cognitive and psychomotor areas are worked in various areas such as the clinical or the educational.
Keywords: Music; medicine; benefits.